Telegram (copy) - Citrine, Walter, 1887-1983
010-0144-001 11th August, 1936. Telegram to Comorera, Barcelona, Fortuny 15. "Received your telegram yesterday only because of my absence from London. I am extremely busy with Trade Union work here. Will you please explain more fully by letter or telegram nature of matter you wish me to discuss." Citrine. 292/946/10/157